Quality and shelf life of low fat restructured turkey meat loaf - Naseera A P (Department of Livestock Products Technology, College of Veterinary and Animal Sciences, 2007)
The health conscious consumers prefer low fat meat products and therefore, the present study was designed to develop a suitable formulary for low fat restructured turkey meat loaf and to assess its physico-chemical and cooking characteristics, sensory qualities, proximate and mineral composition, nutritional value, shelf life and cost of production. Four different formulations, viz., low fat control loaf without fat or fat replacer (LFC), added fat control loaf with 10 per cent sunflower oil added on meat weight basis (AFC), low fat loaf with 0.2 per cent carrageenan (CG) and low fat loaf with 4 per cent nonfat dry milk (NFDM) using skinless lean white and dark turkey meat (2:1), curing ingredients, spices and condiments were prepared. The baked loaves were sliced, packaged aerobically and under vacuum in high density polyethylene and polyamide-polyethylene pouches, respectively. The shelf life of the loaves at 0-4oC for 40 days and -20oC for 60 days were evaluated based on 2-thiobarbituric acid reactive substances value (TBARS), sensory qualities, moisture, protein and fat contents.